Determinan Pertumbuhan Produksi Industri Pakaian Jadi di Kota Denpasar - Laksmi, Wayan Krissyang; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 1, Januari 2018 (pp. 1 - 211), 2018)
Being the capital city of Bali province, it does not make Denpasar has the largest production in the apparel industry sector. The number of workers and clothing business units in Denpasar City is the largest number in Bali Province. This study aims to determine the simultaneous and partial effects between labor, capital and technology variables on clothing industry production in Denpasar City. The population of this research is the whole business of apparel industry in Denpasar City in  2016, the number of samples in the research are 87 respondents,in which that amount determined by Slovin approach with proportional stratified random sampling method. The analysis technique used in this research is multiple linear regression. Based on the results of data analysis it found that simultaneously and partially, variable labor, capital and technology have a positive and significant effect on apparel production in the city of Denpasar. Then, the apparel industry that uses modern technology produces more production than the apparel industry that still uses traditional technology.